PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR TRANSPORTASI YANG TERDAFTAR DI BEI PERIODE 2018-2021 - KHOIRINNISA, NURUL; Amin Setio Lestiningsih (Politeknik Negeri Jakarta, 2024)
The transportation company is one of the companies affected by Covid-19 due to the PSBB which has resulted in a significant decrease in the transportation company's income so that financial distress can occur. The purpose of this study is to examine and analyze the effect of financial ratios on financial distress partially and simultaneously. The research object used is a transportation company listed on the IDX for the 2018-2021 period. The type of research conducted is descriptive quantitative. The samples were obtained after using a purposive sampling approach, namely 27 companies and a total of 100 observational data. In this study there are four, namely Liquidity (CR), Leverage (DAR), Profitability (ROA), Activity (FAT) as independent variables and financial distress (Z-Score) as the dependent variable. The analysis technique used is descriptive statistics, classical assumption test, multiple linear regression, F test, T test and coefficient of determination test. The results showed that the liquidity ratio had a positive effect on financial distress, the leverage ratio had a negative effect on financial distress, the profitability ratio had a positive effect on financial distress, and the activity ratio had a positive effect on financial distress. And simultaneously the variables of liquidity, leverage, profitability and activity affect financial distress with a significance value of 0.000 < 0.05. Keywords: liquidity, leverage, profitability, activity, financial distress